Determination of Fluoxetine in Hospital Wastewater Using Solid-Phase Microextraction Fiber Coated With SWCNT - Mahdi Khoshnood; Mohammad Naimi-Joubani; Behzad Chahkandi; Mahmoud Ebrahimi (Hamadan University of Medical Sciences, 2018)
Fluoxetine is used as an effective antidepressant in psychopharmacology. As a pharmaceutical and personal care product (PPCP) found in superficial waters, fluoxetine influences the wildlife that inhabit these waters. This study was conducted to determine the fluoxetine concentration even in trace quantity in the hospital wastewater, using a solid-phase microextraction (SPME) silica fiber layered with single-walled carbon nanotubes (SWCNTs). An instrumental setup including off-line SPME, which uses a simple carbon nanotube (CNT) to bond capillary column combined with fluorescence spectrometry, was arranged as a sensitive method for the quantification of fluoxetine in real sample. A one at-a-time optimization strategy was applied for optimizing extraction parameters such as extraction time, stirring rate, desorption time, pH, and salt effect on the extraction, preconcentration and determination of fluoxetine in aqueous samples. The advantages of the developed method were: being simple to use with shorter amounts of time for analysis, lower equipment costs, thermal stability of fiber, and high relative recovery in contrast to conventional methods of analysis. Linear ranges were within 0.1-30 µg/L and the detection limit for the fluoxetine was 1×10-4 µg/L.